Development and preliminary validation of Cancer-related Psychological Flexibility Questionnaire - Ou, Mei-jun; Xu, Xiang-hua; Chen, Hong; Chen, Fu-rong; Shen, Shuai (Frontiers in Psychology, 2023)
The Cancer-related Psychological Flexibility Questionnaire (CPFQ) was developed and validated for assessing cancer patients' psychological flexibility, including attitudes and behavior toward cancer. In a systematic process, the CPFQ identified four factors through principal component analysis and confirmatory factor analysis: Cancer Acceptance, Cancer Avoidance, Activity Engagement, and Valued Action. The results of this study reveal that the CPFQ has a clear factor structure and good psychometric properties. The specific nature of cancer and the need for a specific measure of cancer patient psychological flexibility make this questionnaire valuable for research on psychological flexibility in cancer patients.